Financial intermediaries and national savings in developing countries - Tun Wai, U. (New York : Praeger, 1972)
The book examined the role of financial intermediation in promoting savings in the organized markets. It also examines some financial institutions that exist in the most of the developing counties and the role that each of them plays in collecting savings.
Includes bibliographical references.
usc 11/7/17
Loans
Keywords: Saving and investment; Finance